Detecting Lactococcus lactis Prophages by Mitomycin C-Mediated Induction Coupled to Flow Cytometry Analysis - Oliveira, Joana; Mahony, Jennifer; Hanemaaijer, Laurens; Kouwen, Thijs R. H. M.; Neve, Horst; MacSharry, John; van Sinderen, Douwe (Frontiers in Microbiology, 2017)
Most analysed Lactococcus lactis strains are predicted to harbor one or more prophage genomes within their chromosome; however, the true extent of the inducibility and functionality of such prophages cannot easily be deduced from sequence analysis alone. Chemical treatment of lysogenic strains with Mitomycin C (MmC) is known to cause induction of temperate phages, though it is not always easy to clearly identify a lysogenic strain or to measure the number of released phage particles. Here, we report the application of flow cytometry as a reliable tool for the detection and enumeration of released lactococcal prophages using the green dye SYTO-9.